2019
DOI: 10.1007/s10973-019-08314-5
|View full text |Cite
|
Sign up to set email alerts
|

Shaping metal–organic framework (MOF) powder materials for CO2 capture applications—a thermogravimetric study

Abstract: The paper presents the effect of the tabletting pressure and time on the chemical structure and crystallinity of the CuBTC and MIL-53(Al) metal-organic framework tablets. For MOFs, the no-binder tabletting method was employed using a pressure of 3.7, 7.4, 29.6 and 59.2 kN m-2 , respectively, for a duration of 0.5, 1 and 2 min. The obtained tablets were crushed and sieved to obtain the desired fraction from 500 to 650 lm. In this study, the thermogravimetric test has been used for the assessment of the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…There is, however, a small shift of the reflections towards larger 2 values. The authors attributed this phenomenon to structural deformations of the framework upon compression, in accordance with the results provided by Majchrzak-Kuceba and Sciubidlo [36]. In addition, it was shown that textural properties were altered accordingly.…”
Section: Introductionsupporting
confidence: 84%
“…There is, however, a small shift of the reflections towards larger 2 values. The authors attributed this phenomenon to structural deformations of the framework upon compression, in accordance with the results provided by Majchrzak-Kuceba and Sciubidlo [36]. In addition, it was shown that textural properties were altered accordingly.…”
Section: Introductionsupporting
confidence: 84%
“…Before S. A. After Process time Ref Binder-free MOF-5 2750 2600 ~ 1200 [166] CPO-27-Ni 1060 1050 30 min [167] CuBTC (Basolite™ C300) [168] MIL-53(Al) [168] HKUST-1 3 h [169] UiO-66 1175 511 / 417 6–18 h [155] HKUST-1 11 h [170] ZIF-8HT 1387 1 d [170] ZIF-8LT 1359 1 d [171] ZIF-8LT-HT 1423 1 d [171] ZIF-8ER 1395 1 d [171] …”
Section: Post-processing Of Mofsmentioning
confidence: 99%
“…This last aspect is not at all trivial, because in literature many MOFs have been subjected to densification processes with or without the help of chemical binders, but in most cases a significant loss of crystallinity and surface area have been found, compromising the typical performances of the material, especially as adsorbent or catalyst. [4,[11][12][13][14][15][16][17][18][19][20][21] Recently, after many unsuccessful attempts, [4,[11][12][13] it has been found that HKUST-1 (or Cu-BTC), which is considered a reference system for all of the copper paddle wheel MOFs like STAM-17-OEt, is actually very easy to compact if the appropriate protocol is applied. [22] However, HKUST-1 is very sensitive to water and it typically undergoes severe hydrolysis even by limited exposure to air.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the new MOF STAM‐17‐OEt (Cu(C 10 O 5 H 8 ) ⋅ 1.6 H 2 O) combines all these extraordinary properties: it is flexible (or better, hemilabile), [7–9] extremely water‐stable, [7,8,10] and with this work we show that it is also very resistant to the mechanical pressures necessary for the industrialization of the material, and therefore easy to densify and commercialize even if originally synthesized in powder form. This last aspect is not at all trivial, because in literature many MOFs have been subjected to densification processes with or without the help of chemical binders, but in most cases a significant loss of crystallinity and surface area have been found, compromising the typical performances of the material, especially as adsorbent or catalyst [4,11–21] . Recently, after many unsuccessful attempts, [4,11–13] it has been found that HKUST‐1 (or Cu‐BTC), which is considered a reference system for all of the copper paddle wheel MOFs like STAM‐17‐OEt, is actually very easy to compact if the appropriate protocol is applied [22] .…”
Section: Introductionmentioning
confidence: 99%